Progress in China's Banking Sector Reform : Has Bank Behavior Changed? - Podpiera, Richard (IMF Working Papers; Working Paper, 2006)
Substantial effort has been devoted to reforming China's banking system in recent years. The authorities recapitalized three large state-owned banks, introduced new governance structures, and brought in foreign strategic investors. However, it remains unclear the extent to which currently reported data reflect the true credit risk in loan portfolios and whether lending decisions have started to be taken on a commercial basis. We examine lending growth, credit pricing, and regional patterns in lending from 1997 through 2004 to look for evidence of changing behavior of the large state-owned commercial banks (SCBs). We find that the SCBs have slowed down credit expansion, but that the pricing of credit risk remains undifferentiated and banks do not appear to take enterprise profitability into account when making lending decisions. Controlling for several factors, we find that large SCBs have continued to lose market share to other financial institutions in provinces with more profitable enterprises. The full impact of the most recent reforms will become clear only in several years, however, and these issues should be revisited in future research.